Adjunct Triptorelin in the Treatment of Obsessive-Compulsive Disorder in Clients Receiving Selective Serotonin Reuptake Inhibitors (SSRIs) - Faezeh Nikzad; Seyed Alireza Sadjadi; Amir Hooshang Mohammadpour; Maliheh Ziaee; Fatemeh Behdani; Seyedeh Maryam Naghibi; Seyedeh Narges Nejatifard; Mahdieh Ghanbari; Ali Akhondpour Manteghi (Iranian Journal of Psychiatry, 2021)
Objective: Analog triptorelin is one of the effective agonists for the treatment of reproductive disorders, particularly prostate cancer. Due to results of previous studies, we hypothesized that obsessive-compulsive disorder (OCD can be effectively treated with the long-term administration of a gonadotropin-releasing hormone (GnRH) analog, namely triptorelin. The aim of this study was to evaluate the effectiveness of triptorelin injection in clients with OCD.